Targeted proteomics reveals compositional dynamics of 60S pre‐ribosomes after nuclear export - Martin Altvater; Yiming Chang; Andre Melnik; Laura Occhipinti; Sabina Schütz; Ute Rothenbusch; Paola Picotti; Vikram Govind Panse (Molecular Systems Biology)
Abstract Construction and intracellular targeting of eukaryotic pre‐ribosomal particles involve a multitude of diverse transiently associating trans‐acting assembly factors, energy‐consuming enzymes, and transport factors. The ability to rapidly and reliably measure co‐enrichment of multiple factors with maturing pre‐ribosomal particles presents a major biochemical bottleneck towards revealing their function and the precise contribution of >50 energy‐consuming steps that drive ribosome assembly. Here, we devised a workflow that combines genetic trapping, affinity‐capture, and selected reaction monitoring mass spectrometry (SRM‐MS), to overcome this deficiency. We exploited this approach to interrogate the dynamic proteome of pre‐60S particles after nuclear export. We uncovered assembly factors that travel with pre‐60S particles to the cytoplasm, where they are released before initiating translation. Notably, we identified a novel shuttling factor that facilitates nuclear export of pre‐60S particles. Capturing and quantitating protein interaction networks of trapped intermediates of macromolecular complexes by our workflow is a reliable discovery tool to unveil dynamic processes that contribute to their in vivo assembly and transport.